TINJAUAN HUKUM ISLAM TERHADAP PEMENUHAN NAFKAH BAGI SUAMI NARAPIDANA TERHADAP KELUARGA STUDI KASUS NARAPIDANA LEMBAGA PEMASYARAKATAN (LAPAS) WONOGIRI - Aziz, Umar Abdul; Baehaqi, B; Sarjono, Joko (AL HUKMU: Journal of Islamic Law and Economics, 2023)
The subject of this research is the obligation to provide for the husband of the convicted husband. Nafkah is an obligation that must be carried out by a husband to his wife in a material form, because the word nafkah itself has a material connotation. Meanwhile, obligations in non-material forms, such as satisfying a wife's sexual desires, are not included in the definition of a living, even though they are carried out by the husband to his wife. This research aims to find out how the obligation to support the husband who is convicted. The stipulation on the amount of income of the convicted husband, takes into account the rich and poor conditions of the husband. Each husband of the convicted person provided a living based on his ability. If the husband who is convicted is a capable person, the income he has to give to his wife is in accordance with his abilities, namely as much as possible to provide the best living for his wife, but still within the level of his ability. And for prisoners who are unable or have a difficult economic life, the minimum income limit for their wives is as much as a person's body cannot stand upright if he is fed less than that.